2015
DOI: 10.4038/tar.v25i4.8059
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cadmium on growth parameters and plant accumulation in different rice (Oryza sativa L.) varieties in Sri Lanka

Abstract: Rice (Oryza sativa L.) has the ability to uptake and accumulate cadmium (Cd)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…A decrease in yield and yield components of the rice cultivar through the application of exogenous Cd has been observed by Kanu et al (2017), and the negative consequences were greatly varied depending on the rice cultivar and levels of Cd toxicity in the soil. Reduction of yield and yield-related components due to Cd toxicity was also reported by Herath et al (2014). The application of Fe in the soil increased the number of tillers per hill, plant height, panicle length, number of filled grains per panicle, straw yield, and grain yield of the rice cultivar, and this was more pronounced in Fe1.0 than Fe2.0 compared to the control (Table 4).…”
Section: Effect Of CD and Fe On Yield And Yield Components Of Rice Cultivarssupporting
confidence: 73%
See 1 more Smart Citation
“…A decrease in yield and yield components of the rice cultivar through the application of exogenous Cd has been observed by Kanu et al (2017), and the negative consequences were greatly varied depending on the rice cultivar and levels of Cd toxicity in the soil. Reduction of yield and yield-related components due to Cd toxicity was also reported by Herath et al (2014). The application of Fe in the soil increased the number of tillers per hill, plant height, panicle length, number of filled grains per panicle, straw yield, and grain yield of the rice cultivar, and this was more pronounced in Fe1.0 than Fe2.0 compared to the control (Table 4).…”
Section: Effect Of CD and Fe On Yield And Yield Components Of Rice Cultivarssupporting
confidence: 73%
“…Compared with other cereals, rice (Oryza sativa L.), which is the principal food for more than half of the world's population, is highly efficient in Cd accumulation and transfer from soil to grain (Shahriar et al, 2020). A high concentration of Cd in cultivated land is a serious environmental issue as the toxicity of Cd can pose a threat to food security, impacting both yield and yield components of rice plants (Meharg et al, 2013;Herath et al, 2014). There are several studies reported that Cd toxicity retarded the growth and biomass of rice plants ( Ahsan et al, 2007;Li et al, 2012;Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (2011) reported that low Cd concentrations could promote plant growth and height of sweet sorghum and experimental sudan grass variety, plant height reached high values at Cd 25 mg/kg while at high concentrations (50 and 100 mg/kg), Cd inhibits the growth of plant height. In other studies in rice, high concentrations of Cd (50 and 100 mg/kg) strongly inhibited the height of the plant (Herath et al, 2014). A study by Liu et al (2014) showed that, after 3 to 7 days of treatment with Cd (25, 50 and 100 mg/kg), the growth of young cotton plants were significantly inhibited, reflecting a sharp drop in height, biomass and leaf area.…”
Section: Effect Of CD On Number Of Leavesmentioning
confidence: 89%
“…Also, morphological changes occur in response to heavy metals in plants (Brandão et al 2018). But Herath et al (2013) reported variety Bg 352 of rice (Oryza sativa L.) increased the root dry weight from 50 to 100 mg Cd/kg, while Rossato et al (2012) reported the no alteration in the dry weight yield of Pluchea sagittalis Lam. plant organs after heavy metal exposure might be connected with synthesis of cell wall polysaccharides.…”
Section: Discussionmentioning
confidence: 99%